Evaluation of the Maturity of Information Technology Governance in an Ecuadorian RuralDecentralised Autonomous Government Using COBIT 2019 (Innovation & Development in Engineering and Applied Science, 2026)
Public institutions face significant challenges in ensuring adequate Information Technology (IT) governance, which is essential for institutional efficiency. This study aimed to propose and validate a methodological model based on COBIT 2019 to measure and improve the maturity of IT processes in the Rural Parish Decentralised Autonomous Government of Tufiño. The methodology employed followed a mixed-methods approach structured into five phases: institutional diagnosis, data collection, maturity assessment, application of design factors, and validation of improvement proposals. The results were validated through the Delphi method in two rounds with ten experts. The findings indicate an initial maturity level of 0.6, revealing significant gaps in relation to the target level of 2.4. The improvement proposal was validated in two Delphi rounds, achieving acceptance rates of 92 % and 100 %. The combined model of COBIT 2019 and the Delphi method made it possible to evaluate the effectiveness of COBIT 2019 in strengthening IT governance in GADP-Tufiño. Its application proved to be effective and replicable in both public and private institutions.
Keywords: IT Governance; Computer Security; COBIT 2019; PILAR